Morphological, structural and cytotoxic behavior of starch/silver nanocomposites with synthesized silver nanoparticles using Stevia rebaudiana extracts - Valera Zaragoza, Mario; Huerta Heredia, Ariana Arlene; Peña Rico, Miguel Angel; Juárez Arellano, Erick Adrián; Navarro Martinez, Ana Karin; Ramírez-Vargas, E.; Sánchez-Valdes, S. (Polymer Bulletin, 2020)
The synthesis of silver nanoparticles (AgNPs) using a Stevia rebaudiana aqueous extract and their dispersion in starch in order to obtain starch/AgNps nanocomposites are shown in this study. The AgNPs and the starch/AgNPs nanocomposites have been characterized by ultraviolet–visible spectroscopy, optical microscopy, high-resolution transmission electron microscopy, scanning electron microscopy, X-ray diffraction, differential scanning calorimetry and thermogravimetric analysis. Furthermore, the interaction of starch/AgNPs nanocomposites with a MCF-7 breast cancer cell line is analyzed. AgNPs with an average size around 15–20 nm have been obtained. starch/AgNPs nanocomposite morphology changes with the content of silver (3, 5 and 8 mM), from totally separated and dispersed nanoparticles to ribbon-type morphology. The diffraction pattern of the starch/AgNPs-3 nanocomposite indicates the formation of silver chloride nanoparticles (AgClNPs). A cytotoxic behavior of starch/AgNPs-3 nanocomposite on MCF-7 cancer cells with less damage to normal cells is observed. Hence, the high dispersion of the AgNPs or AgClNPs in starch could be influencing the selective cytotoxic behavior. Thus, this study proposes the generation of biocompatible composite materials, with AgNPs immobilized on starch. These materials have selective action against breast cancer cells, where the selectivity is controlled through the AgNPs dispersion on the biopolymer.
Keywords: Nanocompuestos; Morfología; Nanopartículas de plata